Labor Position and Its Impact on The Birth Process: A Literature Review - Ahmar, Hamdiah; Sofyana , Sherllia; Suciati , Siti; Ernawati, Ernawati; Liantanty , Firda (Utan Kayu Publishing, 2025)
Variations in labor positions can enhance childbirth by improving maternal comfort, satisfaction, and reducing complications like prolonged labor and perineal trauma. This review aimed to evaluate the impact of labor positions on specific outcomes: duration of labor, perineal integrity, maternal comfort, and medical intervention rates. A systematic literature search was conducted in April 2025 using PubMed, SpringerLink, and ScienceDirect databases, employing keywords such as